A Rare Case of Mullerian Agenesis (Mayer-Rokitansky-Kuster-Hauser Syndrome) - Meher-Un-Nisa, Aleena Surwer, Tayyaba Iqbal, Maria Maqsood, Hina Zafa, Usman Iftikhar (Pakistan Journal of Medical & Health Sciences, 2022)
A 21 years old girl presented in Gyne OPD of Lady Aitchison Hospital Lahore with complaint of primary amenorrhea. There was no complaint of cyclical dysmenorrhea, urinary retention or feeling of abdomino pelvic mass. Her mother had menarche at 14 years of age. Her height was 5 feet and one inch. Her secondary sexual characteristics were of normal (female) and well developed, external genitalia were of female with rudimentary vagina.Ultrasound showed normal size ovaries and hypoplasticuterus and rudimentary vagina.Hormones (FSH, LH, Prolactin) were normal. HerKaryotype was 46XX.On the basis of these findings, diagnosis of Mullerianagenesis (Maye-Rokitansky-Kuster Hauser Syndrome) was made. Family was counselled about the case. They were informed the patient is unable to menstruate and reproduce. However, for sexual function, it is possible to create a new vagina bynon-surgical method using Hegar dilator or surgical by vaginoplasty.